Implantation of a totally implanted venous device unexpected discovery of left permanent superior vena cava in a patient with sigmoid colon cancer: a case report - Shuchen Zhu; Mingyan Dong; Haiguan Luo; Yicui Piao; Qiaohong Zhang; Lihui Huang; Zijie Liu (Frontiers in Surgery)
Persistent left superior vena cava (PLSVC) is an intrathoracic vascular malformation. Sigmoid colon cancer with a left superior vena cava (LSVC) is very rare. Totally implanted venous devices (TIVADs) are commonly used in recurrent chemotherapy for sigmoid colon cancer. We describe a case of unexpected finding of coronary sinus rhythm in intracavitary electrocardiogram localization TIVAD implantation. Intraoperative ultrasonography revealed a PLSVC.